CaNOP 3U CubeSat Electrical Power System: Power Tests - Weber, Austin (Proceedings of the Wisconsin Space Conference, 2019)
The Canopy Near Infrared Observing Project (CaNOP) consists of a 3U CubeSat nanosatellite funded through WSGC. Its mission objective is to capture multispectral images across global forests, similar to that of the Landsat missions. In order to ensure the missionâ€™s success, battery power must be managed efficiently. With newly working code for components in the â€œheader stackâ€, operating and power tests were conducted and results were recorded. These results were fairly consistent with power and current data given within component manuals. This data will be critical in the next stages of testing, where battery life will be limited and actions will need to be taken to ensure the CubeSat does not drain its battery in space.